Spectral albedo and transmittance of thin young Arctic sea ice - Taskjelle, Torbjørn; Hudson, Stephen R.; Granskog, Mats A.; Nicolaus, Marcel; Lei, Ruibo; Gerland, Sebastian; Stamnes, Jakob J.; Hamre, Børge (Journal of Geophysical Research: Oceans, 2016)
Spectral albedo and transmittance in the range 400–900nm were measured on three separate dates on less than 15 cm thick new Arctic sea ice growing on Kongsfjorden, Svalbard at 78:9°N, 11:9°E. Inherent optical properties, including absorption coefficients of particulate and dissolved material, were obtained from ice samples and fed into a radiative transfer model, which was used to analyze spectral albedo and transmittance and to study the influence of clouds and snow on these. Integrated albedo and transmittance for photosynthetically active radiation (400–900 nm) were in the range 0.17–0.21 and 0.77– 0.86, respectively. The average albedo and transmittance of the total solar radiation energy were 0.16 and 0.51, respectively. Values inferred from the model indicate that the ice contained possibly up to 40% brine and only 0.6% bubbles. Angular redistribution of solar radiation by clouds and snow was found to influence both the wavelength-integrated value and the spectral shape of albedo and transmittance. In particular, local peaks and depressions in the spectral albedo and spectral transmittance were found for wavelengths within atmospheric absorption bands. Simulated and measured transmittance spectra were within 5% for most of the wavelength range, but deviated up to 25% in the vicinity of 800 nm, indicating the need for more optical laboratory measurements of pure ice, or improved modeling of brine optical properties in this near-infrared wavelength region. publishedVersion